2015
DOI: 10.1589/jpts.27.1045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mirror therapy with tDCS on functional recovery of the upper extremity of stroke patients

Abstract: [Purpose] This study aimed to determine the effect of mirror therapy (MT) with transcranial direct current stimulation (tDCS) on the recovery of the upper extremity function of chronic stroke patients. [Subjects] Twenty-seven patients at least 6 months after stroke onset were divided randomly into an experimental group (14 patients) and a control group (13 patients). [Methods] All subjects received tDCS for 20 min followed by a 5 min rest. Then the experimental group received MT while the control group conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 15 publications
2
33
0
4
Order By: Relevance
“…Importantly, decreased mouse head volume compared to the rat suggests a further scaling factor – which if ≥ 2 brings this result in line with those in healthy rats. However, it is important to note that several studies in the acute and subacute phase of recovery have been successfully conducted in humans (see above) without reported serious adverse events [186], [152], [153], [187], [188]. …”
Section: Dcs Safety Data From Animal Lesion Studies and Translationalmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, decreased mouse head volume compared to the rat suggests a further scaling factor – which if ≥ 2 brings this result in line with those in healthy rats. However, it is important to note that several studies in the acute and subacute phase of recovery have been successfully conducted in humans (see above) without reported serious adverse events [186], [152], [153], [187], [188]. …”
Section: Dcs Safety Data From Animal Lesion Studies and Translationalmentioning
confidence: 99%
“…In addition, there are few reports of dropouts with 14 from 6 studies [153], [79], [28], [154], [155], [156] out of 507 total participants across 33 studies. Reporting criteria and reasons for dropouts vary and include personal reasons (e.g.…”
Section: Tdcs Special Considerations For Safety In Strokementioning
confidence: 99%
“…Los pacientes con accidente cerebrovascular presentan tono muscular anormal, disminución de la capacidad de control motor, disminución de la capacidad de coordinación, debilidad de la fuerza muscular en la extremidad superior y trastorno sensorial (Cho & Cha, 2015) una extremidad superior parética es una consecuencia común de un accidente cerebrovascular (Park, Chang, Kim, & An, 2015). La literatura reporta que la extremidad superior es la que más se ve afectada en pacientes con accidente cerebrovascular (ACV) y está genera una gran limitación a la hora de desempeñarse en actividades de la vida diaria ya que para la mayoría de estas actividades se requiere el uso de la mano o el brazo (Cho & Cha, 2015) (Jung-Hee & Byoung-hee, 2017) (Park, Chang, Kim, & An, 2015) Se sabe que el mecanismo de recuperación después del accidente cerebrovascular es más prominente en los primeros tres meses. Además, el nivel de recuperación logrado en el primer mes de accidente cerebrovascular determina el resultado funcional en la fase crónica.…”
Section: Resultsunclassified
“…The most widely used instruments for motor function were FMS 10,15,18,19,[22][23][24][25] , BMRS 15,19,23,24 , MFT 15,19,26 and BBT 19,20,23,25 , which assess the gross and fine motor function of the UL. In general, the studies that used these tests showed statistically significant results, with improvement of the group that received MT, in comparison to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies used the Action Research Arm Test, the Jebsen-Taylor Test and the Motricity Index instruments and also verified improvements in the experimental group, compared to the control group 17,20,22,23 . Some of the researches also evaluated the sensorial function 16,18 and aspects such as prehension 25 , kynematics 18 and spasticy 16,20 , with varied instruments. In these studies MT had significant results, with the exception of the studies by Lin et al 20 and Thieme et al 16 , who observed non-significant spasticity improvement and spasticity increase in the finger flexor muscles, respectively, after the intervention.…”
Section: Discussionmentioning
confidence: 99%